2016
DOI: 10.1176/appi.ps.201400471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating START NOW: A Skills-Based Psychotherapy for Inmates of Correctional Systems

Abstract: START NOW was shown to be an effective treatment option for reducing disciplinary infractions by inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
3
21
0
1
Order By: Relevance
“…Peer support demonstrated positive effects on internalized stigma and personal recovery”. Similarly, for the manualised START NOW for offending behaviour the lead validation study [ 79 ] showed that in a retrospective cohort analysis of prisoners, the more sessions attended, the greater the benefit. In a secondary analysis of this non-randomised cohort study [ 80 ] the authors noted “unmeasured external forces concurrent to START NOW may have influenced later hospitalization (for example, other programming).” We believe this is particularly important for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Peer support demonstrated positive effects on internalized stigma and personal recovery”. Similarly, for the manualised START NOW for offending behaviour the lead validation study [ 79 ] showed that in a retrospective cohort analysis of prisoners, the more sessions attended, the greater the benefit. In a secondary analysis of this non-randomised cohort study [ 80 ] the authors noted “unmeasured external forces concurrent to START NOW may have influenced later hospitalization (for example, other programming).” We believe this is particularly important for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Entirely available in the public domain, START NOW was originally designed for low-resource settings and as a psychotherapy for incarcerated individuals who present with mood dysregulation, impulsivity, aggression, and interpersonal discord. A retrospective cohort analysis of 850 patients in state prison demonstrated a significantly reduced risk of disciplinary infractions and future psychiatric inpatient days with a dose response effect [16,17]. Furthermore, START NOW has been associated with reduced risk of criminal recidivism in an evaluation of a specialized alternative-to-incarceration program for individuals with serious mental illness and co-occurring substance use disorder [18].…”
Section: Introductionmentioning
confidence: 99%
“…A treatment evaluation study of the original START NOW intervention in the United States showed that this approach is effective for difficult-to-manage, impulsive and aggressive detainees [63]. Analyses of a mixed-gender sample of inmates ( n  = 946 participation events) indicated that START NOW was effective in reducing the number of disciplinary reports received.…”
Section: Introductionmentioning
confidence: 99%